AN AREA OF RIGHT TRIANGLE FOR TRIGONOMETRY - IDRIS, MOCHAMMAD; SHIDDIQ, MOHAMMAD MAHFUZH; ERIDANI, ERIDANI (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2023)
In this paper, we shall investigate formula of tangent function through determination of area of right triangle and rectangle. The consequence of this formula is used to obtain the other two trigonometric function, i.e. sine and cosine functions. Moreover, we also reprove Pythagorean theorem.